EFFECT OF THIAMETOXAN INSECTICIDE ON COFFEE SEEDLINGS - de Assis, Welinton Blener Pereira; Júnior, Kleso Silva Franco; Brigante, Giselle Prado; da Silva, Tamara Machado; de Souza Dias, Márcio de Souza; Ferreira, Natália Scalco (Revista Brasileira de Engenharia de Biossistemas, 2021)
The objective of this research was to evaluate the growth of coffee seedlings using the insecticide Thiamethoxan at different dosages on Coffea arabica L seedlings. Two formulations of the insecticide Thiametoxan were used, dispersible granules (WG A) and granules (GR B), both diluted in water and treatments consisting of doses: 0% (control), 50%, 100% and 150% for both versions of the insecticide. The experimental design used was in randomized blocks, in a 2 x 4 factorial scheme, with three replications. After 180 days, the following parameters were evaluated: height, length of root and shoot, fresh and dry biomass of the root system and shoot. The use of Thiametoxan, in two applications, influenced the development of the root system, plant height, length and mass of the aerial part of the coffee seedlings in comparison with the control, not being observed the effect of different dosages of Thiametoxan in the development of the root system.